Concepts, Importance, and Challenges of Using Technology to Enhance 21st Century Skills - Poudel, Ishwara; Dahal, Santiram (Namuna Academic Journal, 2025)
The research aimed to explore the concept, importance and challenges of using technology to enhance 21st century skills in higher education. An online Microsoft survey form was created and data were obtained from the university teachers including Education, Management, Arts and Science faculty. The major findings of the research include the concept of 21st-century skills as the wide range of knowledge, skills and behavior that are necessary to cope with the technology-driven changing world. Various frameworks define such skills. However, It includes 4Cs, Information and media literacy, and life and career skills. Similarly, active classroom engagement, collaboration, communication, promoting digital and data literacy, coping skills, and enhancing emotional and social skills are important in integrating technology in the classroom. Lack of technology infrastructure, lack of support and training, high cost associated with acquiring and maintaining ICT equipment, and lack of policy guidelines are major challenges that were explored.